GRAMMAR INSTRUCTION BASED ON INTEGRATED ACTIVITIES CONSCIOUSNESS – RAISING ACTIVITIES PLANNING - Kamayana, I Gusti Nyoman Putra (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTThe paper is a theoretical framework on presenting how to plan grammar instructions by applyingintegrated consciousness raising activities. There are mountains of evidence that many learners ofwhatever age or tendency in learning style are unable to transfer good formal knowledge ofgrammar to effective use . Such discrepancy between knowledge and putting it to use had led usto look for alternative ways of helping teachers to manage the practice of grammar in a moreefficient way . One possible way to do this is by using consciousness - raising activities integratedto the English skills : such as reading and writing . These activities provide students with theopportunity to interactively solve grammar tasks in a communicative way. It is hoped that themodel will be selective in increasing students' knowledge and in providing authentic opportunitiesfor communication.Keywords: Grammar Instruction, Integrated CR ActivitiesABSTRAKMakalah ini merupakan kerangka teoritis untuk menyajikan bagaimana merencanakan instruksitata bahasa dengan menerapkan kegiatan peningkatan kesadaran terpadu. Ada banyak buktibahwa banyak pelajar dari segala usia atau kecenderungan dalam gaya belajar tidak dapatmentransfer pengetahuan formal tata bahasa yang baik ke penggunaan yang efektif. Perbedaanantara pengetahuan dan penerapannya telah mendorong kami untuk mencari cara alternatif untukmembantu guru mengelola praktik tata bahasa dengan cara yang lebih efisien. Salah satu carayang mungkin untuk melakukannya adalah dengan menggunakan kegiatan peningkatan kesadaranyang terintegrasi dengan keterampilan bahasa Inggris: seperti membaca dan menulis. Kegiatanini memberikan siswa kesempatan untuk memecahkan tugas tata bahasa secara interaktif dengancara yang komunikatif. Model ini diharapkan selektif dalam meningkatkan pengetahuan siswa dandalam memberikan kesempatan komunikasi yang otentik.Kata Kunci: Instruksi Tata Bahasa, Kegiatan CR Terintegrasi